2021
DOI: 10.1038/s41467-021-26863-y
|View full text |Cite
|
Sign up to set email alerts
|

Distinct RPA domains promote recruitment and the helicase-nuclease activities of Dna2

Abstract: The Dna2 helicase-nuclease functions in concert with the replication protein A (RPA) in DNA double-strand break repair. Using ensemble and single-molecule biochemistry, coupled with structure modeling, we demonstrate that the stimulation of S. cerevisiae Dna2 by RPA is not a simple consequence of Dna2 recruitment to single-stranded DNA. The large RPA subunit Rfa1 alone can promote the Dna2 nuclease activity, and we identified mutations in a helix embedded in the N-terminal domain of Rfa1 that specifically disr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…To test whether origin unwinding requires the endogenous, multimeric context of RPA, we generated an RPA mutant, RPA ΔOB-FΔWH , that contains all four DNA-binding domains but lacks the protein-interaction domains, Rfa1-OB-F and Rfa2-WH (Figure 4A-B). These domains interact with DNA replication and repair proteins but are not involved in DNA binding (Acharya et al, 2021; Collins and Kelly, 1991; Dornreiter et al, 1992; Han et al, 1999; Mer et al, 2000; Prakash and Borgstahl, 2012; Shen et al, 2022; Wold et al, 1989; Zou and Elledge, 2003). Indeed, we found this mutant bound DNA with near wild-type affinity (Figure 4C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test whether origin unwinding requires the endogenous, multimeric context of RPA, we generated an RPA mutant, RPA ΔOB-FΔWH , that contains all four DNA-binding domains but lacks the protein-interaction domains, Rfa1-OB-F and Rfa2-WH (Figure 4A-B). These domains interact with DNA replication and repair proteins but are not involved in DNA binding (Acharya et al, 2021; Collins and Kelly, 1991; Dornreiter et al, 1992; Han et al, 1999; Mer et al, 2000; Prakash and Borgstahl, 2012; Shen et al, 2022; Wold et al, 1989; Zou and Elledge, 2003). Indeed, we found this mutant bound DNA with near wild-type affinity (Figure 4C).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, RPA could also stimulate CMG processivity on ssDNA. Although RPA modulates the activity of other helicases through direct interactions (Acharya et al, 2021; Shorrocks et al, 2021), the ability of EcSSB and RPA ΔOB-FΔWH to substitute for RPA suggests a direct protein-protein interaction between RPA and the helicase are not required. Instead, we consider that RPA stimulates CMG by interacting with the excluded strand.…”
Section: Discussionmentioning
confidence: 99%
“…We next decided to address the role of RPA itself, as it has served as a respectable indicator of Scc2 recruitment. Integral to the preservation of ssDNA at broken DNA ends, it has been shown that RPA enforces the correct polarity of DNA end resection and promotes the recruitment and activity of Dna2 (65). To this end, we made use of the rfa1-G77E allele, characterized as the Saccharomyces cerevisiae equivalent to the fission yeast rfa1-G78E allele (66,67), shown to exhibit markedly reduced affinity of RPA for short ssDNA fragments, and a slightly reduced affinity for longer stretches.…”
Section: Rpa and Rad51 Impede Binding Of Scc2 At The Dsbmentioning
confidence: 99%
“…For DNA binding experiments with linear single-stranded DNA, oligonucleotide X12-3 HJ3 (93 nt) was labeled at the 5' terminus with [γ-32P] (Hartmann-Analytic) and T4 polynucleotide kinase (New England Biolabs), according to standard protocols 65 A major portion of the DNA unwinding experiments were performed using 5' overhang-M13 based circular DNA. This was prepared using oligonucleotide (M13-5'-dT 40 overhang) containing a 37 nt-long region complementary to the M13mp18(+) strand (nucleotides 6289-6326), as well as a 40 nt-long tail at the 5' end, which was annealed to M13mp18 ssDNA 39 .…”
Section: Dna Substrate Preparationmentioning
confidence: 99%